Special Services of Integrated Islamic High Schools in Improving Education User Satisfaction in North Sumatra Province - Pohan, Muhammad Munawir; Latif, Mukhtar; Rosyadi, Kemas Imron (CV. Pusdikra Mitra Jaya, 2024)
This study aims to analyze the special services of Integrated Islamic High Schools in improving education user satisfaction in North Sumatra Province. This research uses qualitative research methods with a case study approach. The research subjects in this paper are principals, teachers, education personnel, parents, students, and alumni. Data collection consists of primary and secondary data. Primary data in this study contains four types of data, namely: interviews (semi-structured), observations, documents, and audio-visual materials. Meanwhile, secondary data is taken from library materials including books, online articles, online news, and school websites, all of which are related to the research objectives. Data analysis techniques start from validating the accuracy of information, transcribing data, preparing data, reading all data, coding data, connecting themes, and interpreting the meaning of themes. The data validity test consists of analyzing data sources, member checking, overcoming bias, using a long duration at the research site, and requesting the help of external auditors to conduct a comprehensive examination of the entire research. The results showed that Integrated Islamic High Schools in North Sumatra Province have a variety of specialized services with varying quality. In general, users are satisfied with the education services offered. However, some areas require improvement, such as teaching methods, school facilities, and technology integration.